IMPLEMENTASI METODE EXTREME PROGRAMMING PADA PENGEMBANGAN SISTEM PELAPORAN KASUS BULLYING DI SEKOLAH BERBASIS WEBSITE - Heryanto, Agus (Universitas Majalengka, 2025)
Bullying in schools remains a serious issue that requires prompt and systematic handling. One of the main challenges in reporting cases is the absence of an integrated system that facilitates both students and school authorities in submitting and following up reports. This study aims to design and implement a web-based bullying case reporting system using the Extreme Programming (XP) development methodology. The research stages include planning, system design with Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), implementation using PHP, HTML, CSS, JavaScript, AJAX, and MySQL database management system, as well as testing through the black box testing method. The results indicate that the developed system effectively supports the reporting process, improves transparency, and simplifies follow-up actions by the school. The black box testing results demonstrate that the system’s functionalities run as expected without significant errors. Therefore, the application of the XP methodology proves to be effective in accelerating the system development process, maintaining flexibility in addressing changing requirements, and delivering a system that meets user expectations. This research is expected to provide a practical solution to support bullying prevention and management in schools through web-based technology.